Application of Laser Capture Microdissection and 16S rRNA Gene Polymerase Chain Reaction in the Analysis of Bacteria Colonizing the Intestinal Tissue of Neonates With Necrotizing Enterocolitis. Issue 10 (October 2015) - Yang, Jingli; Wang, Zhengli; Feng, Jinxing; Ai, Qing; Li, Luquan; He, Yu; Li, Hongdong; Tang, Xiaoli; Yu, Jialin
<x xml:space="preserve">Abstract</x> Background: Necrotizing enterocolitis (NEC) is the most common gastrointestinal emergency in newborns. However, the pathogenesis of NEC remains unclear because most bacterial characterizations of alleged pathogens have been performed via the analysis of human fecal samples and experimental animal studies. The objective is to investigate the microbial composition of NEC using inflamed intestinal tissue surgically removed from neonates diagnosed with NEC (n = 18). Methods: We obtained intestinal tissues via a combination of laser capture microdissection and Gram staining, which was used to mark individual bacteria. Tissues with congenital intestinal atresia (n = 7) served as control specimens. An analysis of the 16S rRNA of each sample was performed via polymerase chain reaction-denaturing gradient gel electrophoresis. Results: Numerous bacteria were observed in the inflamed intestinal wall tissue samples obtained from neonates with NEC following Gram staining and examination under an optical microscope. The total number of types detected by polymerase chain reaction–denaturing gradient gel electrophoresis was 12.17 ± 2.83 per infant with NEC, whereas only 2.57 ± 1.81 types were detected in each infant with congenital intestinal atresia. Proteobacteria had the highest constituent ratio (188 of 285) of all detected clone sequences in the NEC group. Additionally, Pseudomonas sp., Acinetobacter sp., Klebsiella sp., Clostridium sp., Ochrobactrum sp. and Arcobacter sp. were detected only in the NEC group. Conclusions: The combination of Gram staining and laser capture microdissection was a reliable method to obtain and prepare tissue samples for processing. NEC was associated with multiple species of bacteria, and microflora within the disease-affected sites may be relatively specific and stable. Proteobacteria demonstrated the highest constituent ratio. Our observations warrant closer examination of the 6 bacterial genera that were only detected in NEC, particularly Clostridium sp., which may be closely correlated with pneumatosis intestinalis.